A micro-nano synergistic reinforcement, preparation method and reinforced metal matrix composite material

By constructing the nanoparticle distribution area on the surface of microparticles, matching the thermal expansion coefficient and improving thermal conductivity, the problem of thermal stress cracks in existing micro- or nano-reinforced metal-based composites after long-term impact at high temperatures is solved, and the mechanical strength and heat resistance of the composite materials are improved.

CN116121578BActive Publication Date: 2025-03-11SHANGHAI XINENE COMPOSITE ENG TECH CENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310202331.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-06
Publication Date
2025-03-11
Estimated Expiration
2043-03-06

AI Technical Summary

Technical Problem

Existing micro- or nano-reinforced metal-based composite materials are prone to thermal stress cracks after long-term impact at high temperatures, and the mechanical properties of the materials are not significantly improved, and the interface effects are inconsistent, resulting in insufficient mechanical stability and service life in complex environments.

Method used

By constructing the nanoparticle distribution area on the surface of microparticles, the nanophase is used as the transition phase of metal materials and microparticles, matching the thermal expansion coefficient of metal materials and microparticles, improving thermal conductivity, alleviating stress concentration and strain localization, and improving the mechanical strength and thermal shock resistance of composite materials.

Benefits of technology

It effectively solves the problem of mechanical properties degradation caused by stress concentration and localization of strain in composite materials, improves the strength and heat resistance of metal-based composite materials, and enhances the mechanical stability and service life of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application provides a micro-nano synergistic reinforcement, a preparation method and a metal-based composite material reinforced therefrom; the metal-based composite material comprises a two-level structure: the primary structure is a micro-nano synergistic reinforcement region constituted by the micro-nano synergistic reinforcement, the micro-nano synergistic reinforcement is constituted by micron particles and nano phases distributed in the surface region of the micron particles; the secondary structure is a micro-nano multi-scale structure formed by the composite of the primary structure and metal powder; by designing the structure of the micro-nano synergistic reinforcement microregion and improving the matching of the physical properties of the nanophase (such as thermal expansion coefficient and thermal conductivity), the synergistic effect of the micron and nanophases can be used to effectively solve the problem of decreased mechanical properties caused by stress concentration and strain localization in the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, C22C21 / 00, and in particular to a micro-nano synergistic reinforcement, a preparation method and a metal-based composite material reinforced by the same. Background Art

[0002] With the rapid development of technology, the current single metal material can no longer meet the needs of technical fields such as aerospace, chemical industry, mechanical manufacturing, and civil life. How to enhance the mechanical properties of metal materials has always been a hot topic of research. At present, micron or nano-reinforced metal matrix composites can significantly improve the mechanical strength, elastic modulus, temperature change resistance and wear resistance, thermal conductivity and electrical conductivity of metal materials, but there are still many problems, such as: 1. The elastic modulus of micron materials and metal matrix materials is very different, the thermal expansion coefficient is not coordinated, and the wetting effect on metal matrix materials is not good. The micron-reinforced metal matrix composites formed are prone to local strain cracking and thermal stress mismatch; 2. The metal matrix material enhanced by nanomaterials has a high elastic modulus, but it will lead to a decrease in the plastic toughness of the composite material; 3. Although the transition layer in the micro-nano synergistically reinforced metal matrix composite can alleviate the local thermal stress mismatch phenomenon, the structural design of the micron and nano-reinforced area and the metal matrix material is not ideal, and unfused microcrack areas may be formed inside the material, resulting in the transition effect of the dispersed nano-reinforced area is not high, and it is difficult to ensure the mechanical stability and service life of the metal matrix composite in a complex environment.

[0003] Chinese patent CN103866154A discloses a method for dispersing and distributing micro-nano particle reinforcement phases in composite materials, which improves the wettability of the reinforcement to the metal matrix by using low-speed ball milling and high-speed impact, and uses metal powder to wrap the micro-nano phase to reduce the brittle phase formed between the micro-nano and melt interfaces; however, the micro-nano reinforcement area is dispersed in the alloy melt, and when the alloy melt is subjected to mechanical impact, the nano phase may produce defect vacancies, resulting in the subsequent nano phase losing part of the transition effect, and the mechanical properties of the alloy are not significantly improved. Chinese patent CN107999994B discloses a micron / nano particle reinforced composite solder and a preparation method thereof, in which the micron / nano particles are dispersed in the metal solder to refine the nucleation points of the metal grains, and improve the mechanical properties and reliability of the crystallization of the solder joint or weld metal, but the thermal stress coordination of the micro-nano reinforced metal material is still not high.

[0004] Therefore, it is necessary to further optimize the structure of micro-nano reinforced metal-based materials so that the micro-nano particles can fundamentally change the stress-strain field distribution of the metal matrix, strengthen the transition effect of the nano-reinforced phase in the composite material, weaken the interface effect between the micron phase, nano phase and metal material, and increase the durability of the metal-based material to resist external forces. Summary of the invention

[0005] In order to solve the above technical problems, the present invention first provides a micro-nano synergistic reinforcement body, which is composed of micron particles and nano phases distributed in the surface area of ​​the micron particles.

[0006] The present application constructs a nanoparticle distribution area (i.e., nanophase) on the surface of micron particles. The distribution of nanophase can reduce the disparity of performance between micron particles and metal matrix materials in the interface microregion, and improve the performance matching of metal materials and micron particles, and increase the total content of reinforcement. The wettability between micron particles and metal materials is poor, and the nanophase, as a transition phase between micron particles and metal materials, has a small contribution to the interface effect when the distribution thickness on the surface of micron particles is too thin, and cannot solve the problem of wettability; and when the distribution range of the nanophase is too high, it will weaken the effect of micron particles on the metal phase; only by constructing a microregion of appropriate size can the synergistic effect of micron particles and nanophase be utilized to effectively alleviate stress concentration and strain localization in metal materials and improve the comprehensive performance of composite materials.

[0007] Furthermore, the thickness of the distribution area of ​​the nano phase is 1-80% of the radius of the micron particle.

[0008] Preferably, the thickness of the distribution region of the nanophase is 1-50%, more preferably 5-30%, of the radius of the micron particle.

[0009] Furthermore, the average particle diameter of the micron particles is 1-50 μm, preferably 5-25 μm.

[0010] Furthermore, the micron particles include but are not limited to one or more of MoC, WC, Al4C3, B4C, ZrB2, AlN, SiC, B4C, TiC, TiB, TiB2, BN, AlN, TiN, Si3N4, Al2O3, ZrO2, and Al4SiC4C.

[0011] In one embodiment, the micronized particles are MoC.

[0012] In one embodiment, the micron particles are Al2O3 and SiC in a mass ratio of (0.5-2):1.

[0013] Furthermore, the nanophase is formed by the distribution of nanoparticles, and the average particle diameter of the nanoparticles is 5-400nm, preferably 5-200nm.

[0014] Furthermore, the nanoparticles include but are not limited to any one or a combination of nanometal powder, nanooxide, nanoceramic, nanocarbon material, etc.

[0015] Preferably, the nanoparticles are at least one of nanometal powder, nanoceramic and nanocarbon material.

[0016] Furthermore, the thermal expansion coefficient of the nanoparticles is (0-6.5)×10 -6 / K, thermal conductivity is 60-6000W / mk.

[0017] Furthermore, the nano-carbon material includes but is not limited to at least one of carbon nanotubes, carbon nanofibers, carbon nanospheres, graphene, nano-diamonds, and nano-carbon onions.

[0018] Preferably, the nano-carbon material includes at least one of nano-diamond, carbon nanotube, carbon nanofiber and graphene.

[0019] Furthermore, the thermal expansion coefficient of the nanocarbon material is (2-5.5)×10 -6 / K, thermal conductivity is 3000-5600W / mk. The present application found that: although the nanophase distributed outside the micron-reinforced particles can significantly improve the comprehensive performance of metal-based materials, thermal stress cracks will still occur in the composite material after being subjected to high-temperature and long-term impact. In the initial research, the applicant has always used nanoparticles with a lower thermal expansion constant coefficient to coordinate the thermal expansion effect between the micron material and the metal material, but the effect is very small, which may be because the nanophase is not dispersed in the system, but there is a predetermined micro-region structure. The present application is to distribute the nanophase on the surface of the microphase. The nanophase, as a connecting bridge between the metal material and the micron particles, must match the thermal expansion coefficient of the metal material and the micron particles to achieve the best plastic toughness of the composite material, and further define its thermal conductivity, disperse the local high temperature existing in the interface, relieve stress concentration and strain localization, and improve the mechanical strength and heat shock resistance of the composite material.

[0020] Preferably, the nanoparticles are selected from carbon nanotubes and / or graphene.

[0021] Furthermore, the preparation method of the micro-nano synergistic reinforcement body is: high-speed mechanical mixing and assembling of micron particles and nanoparticles at a rotation speed of 500-5000 r / min.

[0022] Furthermore, the volume ratio of the micron particles to the nanoparticles is (4-7):1.

[0023] Furthermore, the high-speed mechanical mixing assembly has a rotation speed of 1000-3000 r / min and a time of 0.5-5 h.

[0024] Preferably, the high-speed mechanical mixing speed is 2000-2800 r / min, and the time is 0.5-3.0 h.

[0025] Secondly, the present application also provides a metal matrix composite material reinforced by a micro-nano synergistic reinforcement body; the metal matrix composite material includes a two-level structure:

[0026] The primary structure is a micro-nano synergistic enhancement zone composed of a micro-nano synergistic reinforcement body; the secondary structure is a micro-nano multi-scale structure formed by the composite of the primary structure and metal powder.

[0027] Furthermore, the micro-nano synergistic reinforcement accounts for 5-45% of the volume of the metal powder, preferably 10-30%.

[0028] Furthermore, the metal powder is a metal alloy powder or a single metal powder.

[0029] Furthermore, the metal alloy includes but is not limited to any one or a combination of titanium alloy, magnesium alloy, cobalt-chromium alloy, iron alloy, iron-nickel alloy, alloyed stainless steel, magnesium-lithium alloy, and nickel-titanium alloy.

[0030] In one embodiment, the metal alloy is an aluminum alloy, including but not limited to at least one of the 1100 series (optional grades include: 1050, 1060, 1100), 2000 series (optional grades include: 2024, 2A16, 2A02), 3000 series (optional grades include: 3003, 3004, 3005, 3103, 3105), 4000 series (optional grades include: 4A01), 5000 series (optional grades include: 5052, 5005, 5083, 5A05), 6000 series (optional grades include: 6061), 7000 series (optional grades include: 7075), and 8000 series (optional grades include: 8011).

[0031] Furthermore, the preparation method of the metal matrix composite material reinforced by the micro-nano synergistic reinforcement body comprises:

[0032] S1. Establishing a primary structure: preparing a micro-nano synergistic enhancement body to form a micro-nano synergistic enhancement region;

[0033] S2. Establishing the secondary structure: Compounding the micro-nano synergistic reinforcement and metal powder by high-speed ball milling;

[0034] S3, cold-pressing, sintering, and thermally deforming the mixed material in S2 to prepare a block.

[0035] Furthermore, when the metal powder is an alloy powder, the added metal powder is an alloy powder compounded with respective metal elements according to corresponding mass contents.

[0036] Furthermore, in S2, the ball milling speed is 300-500 r / min, and the ball milling time is 0.5-3 h.

[0037] Preferably, in S2, the ball milling speed is 400-500 r / min, and the ball milling time is 1-2 h.

[0038] Furthermore, the material-ball ratio during the ball milling process is 1:(15-30).

[0039] Furthermore, in step S3, the green compaction pressure is 450-600 MPa; the sintering temperature is 580-650° C., and the sintering time is 2-4 h.

[0040] Furthermore, in step S3, the thermal deformation temperature is 350-550° C., and the extrusion ratio is 8:1-15:1.

[0041] Beneficial Effects

[0042] 1. This application establishes a micro-nano synergistically enhanced micro-region, in which the nanophase serves as a bridge connecting the microphase and the metal material, better coordinating the mechanical properties of the two, enhancing the bonding strength between the microphase and the metal material, and inhibiting the interface effect in the composite material;

[0043] 2. This application uses the synergistic effect of micro- and nano-phases to effectively solve the problem of reduced mechanical properties caused by stress concentration and strain localization in composite materials by enhancing the structural design of micro- and nano-regions and improving the physical properties of the nano-phase (such as thermal expansion coefficient and thermal conductivity).

[0044] 3. After the micro-nano enhanced region constructed in this application is multi-scale composited with the metal matrix material, the stress field distribution of the metal matrix material can be fundamentally changed, thereby improving the strength and toughness of the metal composite material. DETAILED DESCRIPTION

[0045] Example

[0046] Example 1

[0047] This embodiment provides a metal matrix composite material reinforced by a micro-nano synergistic reinforcement body, wherein the metal matrix composite material comprises a two-level structure:

[0048] The primary structure is a micro-nano synergistic reinforcement zone composed of a micro-nano synergistic reinforcement body, which is composed of MoC micron particles and graphene nanophases distributed on the outer surface thereof, and the thickness of the distribution area of ​​the graphene nanophase is 20% of the radius of the micron particle;

[0049] The secondary structure is a micro-nano multi-scale structure formed by the composite of the primary structure and metal powder;

[0050] The preparation method of the metal matrix composite material is as follows:

[0051] S1. Construction of primary structure (i.e., micro-nano synergistic reinforcement): MoC micron particles (average particle diameter of 8 μm) and graphene nanoparticles (average diameter of 35 μm, thickness of 5.5 nm) were mechanically mixed at a volume ratio of 6:1 to obtain a mixed powder; the mechanical mixing speed was 2000 r / min, and the time was 2 h;

[0052] S2. Construction of secondary structure: 6061 aluminum alloy powder and mixed powder accounting for 15% of its volume are mixed and then high-speed ball milled for lamination. The ball milling speed is 450r / min and the ball milling time is 2h.

[0053] The aluminum alloy powder is prepared by weighing the individual metal powders and mixing them according to the composition of 6061 aluminum alloy (based on the total mass, 0.3% copper, 0.6% silicon, 0.15% manganese, 1.0% magnesium, and the aluminum supplement is 100%);

[0054] S3, cold-press the mixed material in S2 into a green compact at 500 MPa, sinter at 600°C for 3 hours, and then extrude it at 400°C at an extrusion ratio of 12:1.

[0055] Example 2

[0056] This embodiment provides a metal matrix composite material reinforced by a micro-nano synergistic reinforcement body, wherein the metal matrix composite material comprises a two-level structure:

[0057] The primary structure is a micro-nano synergistic enhancement zone composed of a micro-nano synergistic enhancement body, wherein the micro-nano synergistic enhancement body is composed of Al2O3, SiC micron particles (the mass ratio of the two is 1:1) and a graphene nanophase distributed on its outer surface, and the thickness of the distribution area of ​​the graphene nanophase is 30% of the radius of the micron particle;

[0058] The secondary structure is a micro-nano multi-scale structure formed by the composite of the primary structure and metal powder;

[0059] The preparation method of the metal matrix composite material is as follows:

[0060] S1. Construction of the primary structure (i.e., micro-nano synergistic enhancement zone): Micron particles and graphene nanoparticles (average diameter of 35 μm, thickness of 5.5 nm) were mechanically mixed at a volume ratio of 4:1 to obtain a mixed powder; the mechanical mixing speed was 2500 r / min, and the ball milling time was 1.5 h.

[0061] The micron particles are composed of Al2O3 (with an average particle diameter of 10 μm) and SiC (with an average particle diameter of 25 μm) micron particles in a mass ratio of 1:1;

[0062] S2. Construction of secondary structure: 1050 aluminum alloy powder and mixed powder accounting for 30% of its volume are mixed and then laminated by high-speed ball milling. The ball milling speed is 500r / min and the ball milling time is 3h.

[0063] The aluminum alloy powder is prepared by weighing and mixing the metal powders according to the composition of 1050 aluminum alloy (based on the total mass, 0.4% iron, 0.25% silicon, and the aluminum supplement balance is 100%);

[0064] S3, cold-press the mixed material in S2 into a green compact at 600 MPa, sinter at 650°C for 2 hours, and then extrude it at 550°C at an extrusion ratio of 8:1.

[0065] Example 3

[0066] This embodiment provides a metal matrix composite material reinforced by a micro-nano synergistic reinforcement body, wherein the metal matrix composite material comprises a two-level structure:

[0067] The primary structure is a micro-nano synergistic enhancement area composed of a micro-nano synergistic enhancement body, wherein the micro-nano synergistic enhancement body is composed of BN micron particles and a carbon nanotube phase distributed on the outer surface thereof, and the thickness of the distribution area of ​​the graphene nanophase is 5% of the radius of the micron particle;

[0068] The secondary structure is a micro-nano multi-scale structure formed by the composite of the primary structure and metal powder;

[0069] The preparation method of the metal matrix composite material is as follows:

[0070] S1. Construction of the primary structure (i.e., micro-nano synergistic enhancement zone): BN micron particles (average particle diameter of 20 μm) and carbon nanotubes (average diameter of 13 nm, average length of 8 μm) were mechanically mixed at a volume ratio of 7:1 to obtain a mixed powder; the rotation speed was 2800 r / min, and the time was 1 h;

[0071] S2. Construction of secondary structure: 5052 aluminum alloy powder and mixed powder accounting for 10% of its volume are mixed and then laminated by high-speed ball milling. The ball milling speed is 500r / min and the ball milling time is 1h.

[0072] The aluminum alloy powder is prepared by weighing and mixing the metal powders according to the composition of 5052 aluminum alloy (based on the total mass, 2.6% magnesium, 0.25% silicon, 0.3% chromium, and the aluminum supplement is 100%);

[0073] S3, cold-press the mixed material in S2 into a green compact at 450 MPa, sinter at 580°C for 4 hours, and then extrude it at 350°C at an extrusion ratio of 15:1.

[0074] Comparative Example 1

[0075] The method is basically the same as Example 1, except that: the metal matrix composite material is formed by the micron-reinforced phase and the nano-reinforced phase being dispersed in the metal matrix;

[0076] The preparation method is as follows: S1, mixing MoC micron particles (with an average particle diameter of 8 μm) and graphene nanoparticles (with an average particle diameter of 35 μm and a thickness of 5.5 nm) in a volume ratio of 6:1 to obtain a mixed powder;

[0077] S2, mixing 6061 aluminum alloy powder and mixed powder accounting for 15% of its volume, and then high-speed ball milling for compounding, the ball milling speed is 450r / min, and the ball milling time is 2h;

[0078] The aluminum alloy powder is prepared by weighing the individual metal powders and mixing them according to the composition of 6061 aluminum alloy (based on the total mass, 0.3% copper, 0.6% silicon, 0.15% manganese, 1.0% magnesium, and the aluminum supplement is 100%);

[0079] S3, cold-press the mixed material in S2 into a green compact at 500 MPa, sinter at 600°C for 3 hours, and then extrude it at 400°C at an extrusion ratio of 12:1.

[0080] Comparative Example 2

[0081] This embodiment provides a metal matrix composite material reinforced by a micro-nano synergistic reinforcement body, wherein the metal matrix composite material comprises a two-level structure:

[0082] The primary structure is a micro-nano synergistic enhancement zone composed of a micro-nano synergistic enhancement body, wherein the micro-nano synergistic enhancement body is composed of MoC micron particles and graphene nanophases distributed on the outer surface thereof, and the thickness of the distribution area of ​​the graphene nanophase is 90% of the radius of the micron particle;

[0083] The secondary structure is a micro-nano multi-scale structure formed by the composite of the primary structure and metal powder;

[0084] The preparation method of the metal matrix composite material is as follows:

[0085] S1. Construction of primary structure (i.e., micro-nano synergistic reinforcement): MoC micron particles (average particle diameter of 8 μm) and graphene nanoparticles (average particle diameter of 35 μm, thickness of 5.5 nm) were mixed in a volume ratio of 0.5:1 and then ball-milled to obtain a mixed powder; the ball-milling speed was 220 r / min and the ball-milling time was 9 h;

[0086] The rest is consistent with Example 1.

[0087] Comparative Example 3

[0088] It is basically the same as Example 1, except that the speed of high-speed mechanical mixing in S1 is 400 r / min.

[0089] Comparative Example 4

[0090] The method is basically the same as Example 1, except that the graphene is replaced by diamond powder, and the average particle diameter is 180 nm.

[0091] The material-to-ball ratio in the above ball milling process is 1:25. The MoC is purchased from Shanghai Chaowei Nanotechnology Co., Ltd.; the Al2O3 is purchased from Luoyang Zhongchao New Materials Co., Ltd.; the SiC is purchased from Henan Sicheng Grinding Technology Co., Ltd.; the carbon nanotubes are purchased from Jiangsu Tiannai Technology Co., Ltd.; the BN is purchased from Henan Zetai New Materials Co., Ltd.; and the graphene is purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.

[0092] Performance testing method:

[0093] Mechanical properties test: The material was made into tensile specimens according to the national standard "GB / T 228.1-2010 Test method for tensile test of metallic materials at room temperature" and tested by a hydraulic universal material testing machine (model: zwick / Roell Z100) with a loading rate of 2mm / min; the yield strength, tensile strength and elongation of the composite material were measured according to the requirements of GB / T228.1-2010 national standard;

[0094] The test results are shown in Table 1.

[0095] Table 1

[0096] Sample No. Tensile strength / MPa Elongation / % Yield strength / MPa Example 1 400 9.0 320 Example 2 280 12 205 Example 3 353 11 294 Comparative Example 1 350 3.5 300 Comparative Example 2 317 4.2 252 Comparative Example 3 322 4.1 260 Comparative Example 4 405 1.3 380

Claims

1. A metal matrix composite material reinforced by a micro-nano synergistic reinforcement, characterized in that: The metal matrix composite material comprises a two-level structure: The primary structure is a micro-nano synergistic enhancement zone composed of a micro-nano synergistic enhancement body; the secondary structure is a micro-nano multi-scale structure formed by the composite of the primary structure and metal powder; The preparation method of the metal matrix composite material comprises: S1. Establishing a primary structure: preparing a micro-nano synergistic enhancement body to form a micro-nano synergistic enhancement region; S2. Establishing the secondary structure: Compounding the micro-nano synergistic reinforcement and metal powder by high-speed ball milling; S3, cold pressing, sintering, and thermally deforming the mixed material in S2 to prepare a block; In S2, the ball milling speed is 300-500 r / min, and the ball milling time is 0.5-3 h; The micro-nano synergistic reinforcement is composed of micron particles and nano phases distributed on the surface of the micron particles; the thickness of the distribution area of ​​the nano phase is 1-80% of the radius of the micron particle; the nano phase is distributed by nano particles, and the thermal expansion coefficient of the nano particles is (0-6.5)×10 -6 / K, thermal conductivity is 60-6000W / mk; The preparation method of the micro-nano synergistic reinforcement body is: high-speed mechanical mixing and assembling of micron particles and nano particles at a rotation speed of 500-5000 r / min.

2. The metal matrix composite material reinforced by micro-nano synergistic reinforcement according to claim 1, characterized in that: The average particle diameter of the micron particles is 1-50 μm; 3. The metal matrix composite material reinforced by micro-nano synergistic reinforcement according to claim 1, characterized in that: The nanoparticles are at least one of nanometal powder, nanoceramic and nanocarbon material.

4. The metal matrix composite material reinforced by micro-nano synergistic reinforcement according to claim 1, characterized in that: The thermal expansion coefficient of the nanocarbon material is (2-5.5)×10 -6 / K, thermal conductivity is 3000-5600W / mk.

5. The metal matrix composite material reinforced by micro-nano synergistic reinforcement according to claim 1, characterized in that: The micro-nano synergistic reinforcement accounts for 5-45% of the volume of the metal powder.

Citation Information

Patent Citations

  • Method for diffusely distributing micro-nano particle reinforced phase in composite material

    CN103866154A

  • Micron / nanoparticle reinforced composite solder and its preparation method

    CN107999994B

  • Micro-nano composite configuration aluminum matrix composite material and preparation method thereof

    CN112680636A